2022
DOI: 10.1108/rpj-07-2021-0179
|View full text |Cite
|
Sign up to set email alerts
|

Laser additive manufacturing of bulk and powder ceramic materials: mathematical modeling with experimental correlations

Abstract: Purpose This paper aims to develop efficient and simple models for thermal distribution, melt pool dimensions and controlled phase change in the laser additive manufacturing (AM) of bulk and powder particles ceramic materials. Design/methodology/approach This paper proposes new analytical models for the AM of bulk and powder bed ceramic materials. A volumetric moving heat source, along with the complete melting of bulk and powder particle materials, is taken into account. Different values of laser absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…More recently, several authors have presented modeling results combined with experimental measurements on materials other than metals, such as polymers. Concerning ceramic materials, only a few studies comparing numerical model/experimental results have been found in the literature. However, we can cite the work of Mahmood et al, who developed a mathematical model using MATLAB software to study the temperatures reached during laser sintering on a bulk substrate of silicon nitride (Si 3 N 4 ) and on a alumina powder bed (Al 2 O 3 ) . With their numerical model, they can predict the temperature distribution during the laser radiation–matter interaction with 8% accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, several authors have presented modeling results combined with experimental measurements on materials other than metals, such as polymers. Concerning ceramic materials, only a few studies comparing numerical model/experimental results have been found in the literature. However, we can cite the work of Mahmood et al, who developed a mathematical model using MATLAB software to study the temperatures reached during laser sintering on a bulk substrate of silicon nitride (Si 3 N 4 ) and on a alumina powder bed (Al 2 O 3 ) . With their numerical model, they can predict the temperature distribution during the laser radiation–matter interaction with 8% accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…However, we can cite the work of Mahmood et al, who developed a mathematical model using MATLAB software to study the temperatures reached during laser sintering on a bulk substrate of silicon nitride (Si 3 N 4 ) and on a alumina powder bed (Al 2 O 3 ). 23 With their numerical model, they can predict the temperature distribution during the laser radiation–matter interaction with 8% accuracy. Thus, numerical modeling is appropriate to simulate the thermal diffusion inside metallic or polymer layers during the SLS process.…”
Section: Introductionmentioning
confidence: 99%